US FOREIGN POLICY IN RESTORING DIPLOMATIC RELATIONS WITH CUBA IN 2015-2016 - Florentina Wulandari Maria Alexandra (Faculty of Social and Political Sciences Universitas Kristen Indonesia, 2019)
At the end of 2014, the United States, under the leadership of President Barack Obama, decided to improve relations with Cuba. The relationship between the two countries has a long history. After 53 years of severing diplomatic ties with Cuba, America finally made a change through the policy of diplomatic relations improvement that began in 2015. This study analyzes the background that encourages the restoration of political ties between the United States and Cuba, examining the implementation of foreign policy forms between the two countries As a result of the restoration of diplomatic relations between the United States and Cuba through diplomatic channels. This research uses foreign policy theory and the theory of international pathways. The research method used is qualitative research with a secondary data source, with a data collection technique through a literature study. The study found that in the policy of restoring the diplomatic relations between the United States and Cuba happened for three main reasons, the first one. President Obama realized that US sanctions to Cuba is a policy that is not successful; the United States no longer wants to lose the market, which was very promising in Cuba. And also, the United States has a ton amount of pressure internationally and domestically, asking them to recover their relations with Cuba. These reasons ultimately implemented through diplomatic channels by both countries. They have implications such as increased bilateral visits, increased investment, and business as well as cultural exchange through communities and students.